Transportation Systems and E-Commerce: Understanding the Relationship - Hana RABBOUCH; Hayet SAADAOUI; Foued SAADAOUI (Communications of International Proceedings, 2020)
Nowadays, the digital transformation of e-commerce businesses is fraught with several challenges. Among these challenges, there are those related to the optimization of the use of transportation and logistics infrastructure and their relationship with the e-commerce sector. A better understanding of this relationship will certainly make better use of both sectors at the same time. In fact, by a digital implementation and an optimal control of the two systems, it thus becomes possible to carry out the management of the inventories or to offer an ever more precise traceability on the order, from its exit of the inventory up to on delivery to the customer. In a quest to better understand the nature of the relationship between transportation, logistics and e-commerce, a state-of-the-art study and a summary of the main surveys and approaches addressing the issue and technology realities in this framework will be explained in this paper.
Keywords: Electronic Commerce – Distribution – Environment – Traffic Management.